Null Mannheim curves in the Minkowski 3-space $Bbb{E}^3 _1$ - Öztekin, Handan B.; Ergüt, Mahmut (My University, 2011)
In this study, we give the deﬁnition of null Mannheim curve with timelike or spacelike Mannheim partner curve in the Minkowski 3-space $Bbb {E} ^3 _1$ . We get the necessary and suﬃcient conditions for the null Mannheim curves. Then we investigate the null and timelike or spacelike generalized helix as the null Mannheim curve and timelike or spacelike Mannheim partner curve, respectively.
Keywords: Matematik; Fizik; Partiküller ve Alanlar